Expert perspectives on the contribution of HIV general practice nursing to the 'extraordinary story' of HIV medicine in Australia. Issue 2 (14th March 2013) - Hopwood, Max; Newman, Christy; Persson, Asha; Watts, Ian; de Wit, John; Reynolds, Robert; Canavan, Peter; Kippax, Susan; Kidd, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Aim This paper explores cultural and professional dynamics of HIV general practice nursing in Australia. It highlights specific contributions that HIV general practice nurses make to HIV medicine and considers how nurses' clinical practice has been shaped by past experiences of the AIDS crisis and subsequent developments in HIV medicine. Background In international contexts, nurses in HIV medicine commonly work as part of shared-care teams. In recent years, HIV general practice nursing has become a prioritised area for primary health care in Australia. Methods Data for this analysis were drawn from 45 in-depth, semi-structured interviews conducted with nurses and general practitioners (GPs) who provide HIV care in general practice, and key informants who work in policy, advocacy or education and training of the HIV general practice workforce. Findings Viewed through a socio-ecological framework of social capital, descriptive content analysis highlights a unique and strong HIV health professional identity, which emerged out of the adverse conditions experienced by nurses, GPs and allied health professionals during the 1980s AIDS crisis. Participants reported that today, HIV general practice nursing includes information provision, HIV treatment side-effect management, teaching patients methods to increase adherence to HIV treatments and capacity building with allied health professionals. Participants reported that HIV general practice nurses can reduce the clinical burden on GPs, ameliorate patients' exposure to HIV health care-related stigma and discrimination and facilitate the emergence of a comprehensive and personalised model of shared primary health care based on trust and rapport, which is desired by people with HIV. This study's findings support the future expansion of the role of HIV general practice nurses in Australia and internationally. General practice nursing will become increasingly important in the scaling up of HIV testing and in caring for increasing numbers of people living with HIV.